The impact of compliance on the ready-made garments sector in Bangladesh: a descriptive analysis - Akter, Afroza (BOHR International Journal of Finance and Market Research, 2025)
Ensuring compliance within the ready-made garments (RMGs) sector is one of the primary concerns for international buyers and global institutions. Bangladesh’s RMG factories must enhance compliance within their workplaces to maintain a strong position in the global market. This research highlights the impact of compliance issues identified by international stakeholders on the working environment of the RMG industry in Bangladesh. The study employed an interview method along with a simple random sampling technique to gather information from 318 respondents in Dhaka City. Collected data were analyzed using statistical methods, including frequency distributions, and the research hypothesis was examined through the application of the chi-square test. The investigation’s outcomes indicate that factories adhering to compliance guidelines are more likely to uphold workers’ rights according to international labor standards, and their workplace environments are of higher quality than those of factories that are not compliant. After practical observation, it is clear that compliance has influenced the working environment of the RMG industry in Bangladesh, as the accidents that occurred in garment factories were a direct consequence of the inadequate working conditions in RMG factories. Following these incidents, international actors initiated several measures related to workers’ safety. Currently, the situation in both RMG factories is better than before. Although non-compliant RMG factories are still failing to protect workers’ safety rules properly, some rights have now been ensured that were previously unavailable. Therefore, matters related to the advancement of the RMG sector must be effectively addressed to ensure sustainability in the global market.